Exploring the Eco-Friendly Potential of Local Aggregates: A Study on the Use of Senoni Stone and Mahakam Sand in Asphalt Concrete Mixes - Mabui, Didik S.; Tumpu, Miswar; Abas, Azlan; Irianto, .; Eswan, . (Engineering, Technology & Applied Science Research, 2025)
This study investigates the potential environmental benefits of employing locally produced materials, such as Senoni Stone (SS) and Mahakam Sand (MS), in asphalt concrete mixtures, aiming to achieve a balance between environmental sustainability and performance requirements. Since aggregateσ constitute 75%-85% of the total weight of asphalt mixtures, it serves as a primary component. The aggregates used in the specific mixtures are required to meet the Indonesian National Standard (SNI) specifications. In the current work, the Asphalt Concrete Wearing Course (AC-WC) combination was examined using SS as the coarse aggregate and MS as the fine aggregate, both of which originate from East Kalimantan. The volumetric metrics analyzed include Void in Mix (VIM), Void Mineral Aggregate (VMA), and Void Filled Bitumen (VFB). Asphalt concentration varied, with values of 4.5%, 5%, 5.5%, 6%, and 6.5% with increments of 0.5%. VIM values decreased as the asphalt quantity increased, with the corresponding VIM values being 9.26%, 4.51%, 4.33%, 4.17%, and 3.25%. The VMA values recorded for each asphalt content were 19.18%, 16.05%, 16.97%, 17.92%, and 18.56%, respectively, while the VFB values for the same contents were 51.7%, 71.87%, 74.49%, 76.68%, and 77.86%. It is therefore recommended that locally sourced materials, such as SS and MS, be prioritized in asphalt concrete mixtures to support sustainable construction practices. This approach not only reduces environmental impact, but also enhances resource efficiency and strengthens local economies.